2016
DOI: 10.1016/j.jenvrad.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Variation with socioeconomic status of indoor radon levels in Great Britain: The less affluent have less radon

Abstract: We demonstrate a strong correlation between domestic radon levels and socio-economic status (SES) in Great Britain, so that radon levels in homes of people with lower SES are, on average, only about two thirds of those of the more affluent. This trend is apparent using small area measures of SES and also using individual social classes. The reasons for these differences are not known with certainty, but may be connected with greater underpressure in warmer and better-sealed dwellings. There is also a variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…There is about a 10% difference in mean dose-rate between the highest and lowest Carstairs quintiles, which is much smaller than the corresponding variation for radon (Kendall et al, 2016a).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…There is about a 10% difference in mean dose-rate between the highest and lowest Carstairs quintiles, which is much smaller than the corresponding variation for radon (Kendall et al, 2016a).…”
Section: Discussionmentioning
confidence: 71%
“…lower Carstairs score) in comparison to the birth locations of study subjects. This is almost certainly a consequence of a higher relative participation in the measurement programme by the more affluent (Kendall et al, 2016a), whereas birth records are not so affected, and it will be noted that the difference in the proportions of measurements and births is particularly marked in the most deprived quintile. However, the Carstairs scores for each quintile are similar between the measurement locations and the birth locations so allowance for Carstairs quintile should compensate for this difference in epidemiological analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are clear socioeconomic differences in radon-related awareness, risk perceptions, and behaviors. People from lower SES (Kendall et al, 2016) and rural areas (Hill et al, 2006) are less likely to be aware of the risks of radon exposure. Time-series studies of exposure to air pollution found a higher risk of all-cause mortality for people of lower SES (Lin et al, 2004;Villeneuve et al, 2003).…”
Section: Social and Behaviouralmentioning
confidence: 99%
“…In contrast, people with a higher SES maintain their houses and control or even modify their environment with newer technologies (Vardoulakis et al, 2015). However, a recent study in the UK shows an inverse relation to SES, whereby affluent houses that are air-tight and drought-proof have higher levels of radon (Kendall et al, 2016).…”
Section: Environment and Social Interactionsmentioning
confidence: 99%